Association between hippocampal subfield volumes and working memory in middle-aged and older adult cancer patients - Bi, Ran; Liu, Yue; Zhang, Qiaoyang; Dong, Guanzhong; Xu, Ke; Cao, Yin (Frontiers in Human Neuroscience, 2025)
BackgroundCancer-related cognitive impairment (CRCI) is relatively common among middle-aged and older adult cancer patients, with working memory deficits being particularly prominent. However, the underlying structural basis of hippocampal subregions remains unclear. This study aimed to investigate differences in hippocampal subfield volumes and working memory function between cancer patients and healthy controls, as well as to analyze the correlation between hippocampal structural alterations and working memory impairment.MethodsThe cohort comprised 51 cancer patients and 45 healthy controls. All participants underwent 3D-T1 structural MRI scans and cognitive assessments. Hippocampal subfields were automatically segmented using FreeSurfer 7.4, and their volumes were calculated. Group differences in cognitive test scores were compared. After controlling for total intracranial volume (TIV), analysis of covariance (ANCOVA) was performed to examine differences in hippocampal subfield volumes between groups. Spearman correlation analysis was undertaken to assess the relationship between hippocampal subfield volumes and cognitive test scores in patients with cancer.ResultsCompared with healthy controls, cancer patients exhibited significantly lower scores in the digit span test (DST) total score (U = 716.50, p = 0.001) and digit span forward (DSF) subtest (U = 738.50, p = 0.002). Hippocampal subfield analysis revealed significant volume reductions in the cancer group, particularly in CA3 (F = 8.141, p = 0.005) and CA4 (F = 6.770, p = 0.011). Correlation analysis demonstrated that the volumes of the hippocampal head (r = 0.410, p = 0.003) and hippocampal molecular layer (r = 0.389, p = 0.005) were positively associated with DST scores in cancer patients.ConclusionCancer patients exhibit working memory impairment and hippocampal subfield atrophy. The significant correlation between the volumes of the hippocampal head and molecular layer with working memory performance suggests that these regions may play a critical role in cancer-related cognitive dysfunction.